Role of Entrepreneurial Orientation, Online Marketing Capabilities, and Product Innovation in improving Rural MSME’s Performance during VUCA - Santosa, Allicia Deana; Sugiarti, Rubi’ah; Rahayuningrat, Prahita Sri Sri; Kurniawan, Kurniawan (Jurnal Ilmu Sosial Mamangan, 2025)
The power of the Industrial Revolution 4.0, digitalization, globalization, and unpredictable pressures, such as the COVID-19 pandemic and war, have required humans and organizations to adapt to the changes that will occur. The spread of COVID-19 worldwide and changes in government regulations to reduce the rate of spread have been one of the most significant learning curves, placing people and organizations in an unpredictable environment full of uncertainty, complexity, and ambiguity (VUCA). This research analyzes factors that can support MSME performance through Entrepreneurship Orientation (EO). Marketing Capability (MC), Social Media Marketing (SMM) and Product Innovation (PI). The survey was conducted on MSMEs in East Priangan, West Java, using the purposive sampling method, and the data was analyzed using structural equation modeling. The results show that EO improves product performance and innovation, and product innovation improves the performance of MSMEs. EO also increases MC and SSM